2014
DOI: 10.4049/jimmunol.1302192
|View full text |Cite
|
Sign up to set email alerts
|

Smad and NFAT Pathways Cooperate To Induce CD103 Expression in Human CD8 T Lymphocytes

Abstract: The interaction of integrin αE(CD103)β7, often expressed on tumor-infiltrating T lymphocytes, with its cognate ligand, the epithelial cell marker E-cadherin on tumor cells, plays a major role in antitumor CTL responses. CD103 is induced on CD8 T cells upon TCR engagement and exposure to TGF-β1, abundant within the tumor microenvironment. However, the transcriptional mechanisms underlying the cooperative role of these two signaling pathways in inducing CD103 expression in CD8 T lymphocytes remain unknown. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 56 publications
(63 reference statements)
7
75
1
Order By: Relevance
“…The essential cause of this variation is not clearly understood, but it may reflect interpatient variations in the intratumoral level of TGF-b1 or factors involved in its activation, such as a V integrins (30,31), the number of tumor Ag-specific T cell precursors, or both. Indeed, as mentioned above, engagement of both the TGF-b1 receptor and TCR via an active form of TGF-b1 and the tumor peptide/MHC-I complex, respectively, is required for CD103 induction (11). Thus, TGF-b1, considered as an immunosuppressive cytokine, can control immune responses to viral infections and tumors via induction of CD103 and formation of CD8 + CD103 + T RM T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential cause of this variation is not clearly understood, but it may reflect interpatient variations in the intratumoral level of TGF-b1 or factors involved in its activation, such as a V integrins (30,31), the number of tumor Ag-specific T cell precursors, or both. Indeed, as mentioned above, engagement of both the TGF-b1 receptor and TCR via an active form of TGF-b1 and the tumor peptide/MHC-I complex, respectively, is required for CD103 induction (11). Thus, TGF-b1, considered as an immunosuppressive cytokine, can control immune responses to viral infections and tumors via induction of CD103 and formation of CD8 + CD103 + T RM T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that CD103 expression on TIL is associated with increased survival in high-grade serous ovarian cancer (10). This integrin is induced on CD8 + T lymphocytes upon TCR engagement and exposure to TGF-b1, abundant within the tumor microenvironment, through binding of NFAT-1 and Smad2/3 transcription factors to the promoter and enhancer elements of the ITGAE gene that encodes CD103 (11).…”
Section: Ytotoxic T Lymphocytes Play a Major Role In Antiviral Andmentioning
confidence: 99%
“…One signal reported to play a role is transforming growth factor (TGF)‐β1. TGF‐β1 induces CD103 expression through nuclear factor of activated T cells (NFAT)‐1 and suppressor of mothers against decapentaplegic (Smad)2/3 transcription factors binding to the promoter region of the ITGAE gene, encoding for CD103 [5]. Correspondingly, a similar effect has been demonstrated in TGF‐β‐rich tumours, in which T RM cells are consequently generated [6].…”
Section: Introductionmentioning
confidence: 99%
“…1C). Mokrani et al (20) reported that CD103 expression is induced by signaling through Smad and NFAT pathways in human CD8 T cells. However, the mechanism by which TGF-b1 suppresses the expression of FcεRI and c-Kit on the mast cell surface is unknown.…”
Section: Tgf-b1 Suppresses Fc«ri and C-kit Expression In Mast Cellsmentioning
confidence: 99%
“…TGF-b signaling is mediated by Smads, which accumulate in the nucleus to transcriptionally regulate TGF-b target genes. The promoter and enhancer element of Itgae, encoding CD103, are known to have Smad-binding elements (20). Thus, CD103 expression is directly regulated by TGF-b/Smad signaling.…”
mentioning
confidence: 99%